Role of fantasy in emotional clarity and emotional regulation in empathy: A preliminary study - Shiota, Shoichi; Nomura, Michio (Frontiers in Psychology, 2022)
Fantasy is the experience of identifying with characters in movies, novels, plays, and other fictional situations. In social contexts, individuals take on perspective of others by sensing their emotions through empathy. During this process, perspective-taking and emotional sharing affect one’s metacognition, which deals with the distinction between and the understanding of one’s emotions (clarity) and their regulation (repair); previous studies have primarily focused on these processes. However, perspective-taking—considering another individual’s viewpoint—requires one to imagine their outlook; it also induces emotional responses. This study examined the role of fantasy in clarity and repair in metacognition, for which data derived from 475 Japanese participants were analyzed. The results of the Interpersonal Reactivity Index showed that fantasy was positively associated with clarity and repair in the Trait Meta-Mood Scale; these relationships were moderated by perspective-taking and personal distress. Our results revealed that the emotions experienced within oneself might be understood as the distinction between “imagining” (through their imagination; e.g., internal or mental pictures) and “imaging” (from an image; e.g., external pictures). Individuals imagine their immersion into others using lower-level automatic body sensations (emotional contagion), and the accompanying negative emotions are regulated by metacognition.